From policy to practice: the issues and challenges in urban design policies implementation in Malaysia - Hussin, Natasha Azim; Mohd. Hussain, Mohd. Ramzi; Md Jani, Haza Hanurhaza (Otago Polytechnic, 2025)
Urban design policies play an important role in creating sustainable, livable and inclusive cities. They provide a framework to guide the physical, social and environmental aspects of urban growth while making sure development follows long term planning goals. This paper examining the issue and challenges in urban design policies implementation with a particular focus on local authorities in Malaysia. It also explains the conceptual understanding on policy implementation and urban design policy and why it is important for improving city quality, identity and livability. The review discusses the evaluation on models and theories of policy implementation by various scholars which help to explain the challenges and opportunities in putting urban design policies into practice. While many global cities have developed effective systems to ensure urban design policies are consistently applied, Malaysia continues to face challenges in translating policies into practice. Despite the existence of detailed policy documents and design guidelines, gaps remain between written policies and actual implementation, particularly at the local authority level